1979
DOI: 10.1002/jobm.19790190309
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by glycine of the catabolic reduction of proline in Clostridium sticklandii: Evidence on the regulation of amino acid reduction

Abstract: The growth of Clostridium sticklandii on the substrate pair L-alanine-L-proline (redoctanthsidant each 40 m31) in a medium containing 2 g/l yeast extract was completely inhibited by equiniolar amounts of glycine, although glycine itself should be used as oxidant by the cells. The effect, of glycine was t.he same, whether L-alanine. L-arginine, or L-serine were used as reducdants. Performance of the growth experiments in media of high osmolarity excluded the possibility that the inhibition effect,ed by glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Glycine is known to inhibit the synthesis of a peptidoglycan component of the bacterial cell wall (Hishinuma et al, 1969). Although the bacterial cell wall is thinner in gram-negative bacteria than in gram-positive bacteria, it is thought that the amount of glycine required to suppress bacillus proliferation is lower than that required to suppress gram-positive bacteria (Schwartz et al, 1979). Hops extracts possess antimicrobial activities against Streptococcus mutans and other streptococci (Bhattacharya et al, 2003), and salmon roe protein has been shown to have a certain degree of antimicrobial activity against gram-negative and gram-positive bacteria (Anonymous, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Glycine is known to inhibit the synthesis of a peptidoglycan component of the bacterial cell wall (Hishinuma et al, 1969). Although the bacterial cell wall is thinner in gram-negative bacteria than in gram-positive bacteria, it is thought that the amount of glycine required to suppress bacillus proliferation is lower than that required to suppress gram-positive bacteria (Schwartz et al, 1979). Hops extracts possess antimicrobial activities against Streptococcus mutans and other streptococci (Bhattacharya et al, 2003), and salmon roe protein has been shown to have a certain degree of antimicrobial activity against gram-negative and gram-positive bacteria (Anonymous, 2008).…”
Section: Introductionmentioning
confidence: 99%